2019
DOI: 10.25267/rev_eureka_ensen_divulg_cienc.2019.v16.i2.2602
|View full text |Cite
|
Sign up to set email alerts
|

¿Cómo cambian las ideas de los estudiantes de Máster de Profesorado sobre una actividad práctica de campo tras su vídeo-análisis y discusión en pequeños grupos?

Abstract: Resumen: Los trabajos prácticos de campo en la formación inicial del profesorado de secundaria deberían incluir actividades que fuesen más allá de la propia realización de experiencias aplicables en un aula. El presente trabajo analiza las ideas declaradas por un grupo-clase de 16 estudiantes del Máster de Profesorado en diferentes momentos de un conjunto de actividades prácticas. En él, responden a cuestiones sobre la secuencia de actividades realizada y su posible transposición a un aula de secundaria, tanto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…This academic-industry link not only includes the possible resolution of industrial problems, but also the development of better oral and written communication skills due to the direct contact with potential future employers [56]. Another advantage of incorporating LOtC strategies into college chemistry courses is that these experiences could have a positive impact on students' interest in continuing with graduate studies [57]. This is because students obtain access to all types of resources and professionals that might help them identify topics of their interest in the study of chemistry, which may ultimately motivate them to consider the possibility of becoming researchers or scientists in these subjects [57].…”
Section: Previous Studiesmentioning
confidence: 99%
“…This academic-industry link not only includes the possible resolution of industrial problems, but also the development of better oral and written communication skills due to the direct contact with potential future employers [56]. Another advantage of incorporating LOtC strategies into college chemistry courses is that these experiences could have a positive impact on students' interest in continuing with graduate studies [57]. This is because students obtain access to all types of resources and professionals that might help them identify topics of their interest in the study of chemistry, which may ultimately motivate them to consider the possibility of becoming researchers or scientists in these subjects [57].…”
Section: Previous Studiesmentioning
confidence: 99%
“…Another aspect that does not coincide with the studies carried out to date is that it seems that the preference for videos, over taking photos, has been taking place among young people in recent years [35,[55][56][57], which already in this study is not so clear; thus, although there are some tests in which this is confirmed, the same does not happen with the BookFace test (F03), which triumphs over others that involve the making of a video.…”
Section: Discussionmentioning
confidence: 99%
“…A partir de los cuestionarios cumplimentados se analizaron cualitativamente el tipo de respuestas dadas por los estudiantes. Para ello, se ha tomado como marco de referencia a Sáez Bondía y Cortés Gracia (2019), que desde el contexto del Máster de profesorado analizan el tipo de respuestas en una actividad similar. Asimismo, se tuvieron en consideración los resultados del análisis de la puesta en marcha de la misma secuencia en las aulas de Primaria (Lucha López y Sáez Bondía, 2019;Sáez Bondía et al, 2018).…”
Section: Preguntas Planteadasunclassified